Download presentation

Presentation is loading. Please wait.

Published byJonathan Higgins Modified over 6 years ago

1
Working with square roots warm up 1.√3 + √3 = 2.√4 +√4 = 3.√5 + √5 = 4.√1 + √1 = 5.(√3) (√3) = 6.(√5) (√6) = Simplify 7. √24 = 8.√18 = 9.√81 = 10.√150 = 1. 2 √3 2.4 3.2 √5 4.2 5.√9 = 3 6.√30 7.2 √6 8.3 √2 9.+ or – 9 10. 5√6

2
Let’s try some more 1.12 2 + 3 2 2.√36 + √4 3.(√5)(√10) 4.(√18)(√3) 5.(√6)(√8)(√12) 1.153 2.8 3.5√2 4.3√6 5.24

3
Geometry 1 st Semester BOE Review

4
Pythagorean Theorem a 2 + b 2 = c 2 a and b are LEGS of a right triangle. LEGS are those segments that create a right angle. c is the HYPOTENUSE. The HYPOTENUSE is the segment across from the right angle.

5
LEG HYPOTENUSE RIGHT ANGLE a b c If a = 5 and b = 8, find c If a = 2 and c = 8, find b If b = 1 and c = 5, find a c = √89 b = √60 = 2 √15 a = √24 = 2√6 LET’S PRACTICE

6
Cool things you should remember about triangles ♥if c 2 = a 2 + b 2 you have a right triangle ♥if c 2 > a 2 + b 2 you have an obtuse triangle ♥if c 2 < a 2 + b 2 you have an acute triangle ♥in a right triangle, the hypotenuse is always the longest side.

7
What if… What if you had a square with a side measure of 6. What would the length of your diagonal be? 6√2 What if you had an equilateral triangle with side measure of 10. What would the altitude of the triangle be? 5 √3 What would the area of the triangle be? 25 √3

8
Systems of Equations 2 ways to solve: ♥Elimination ♥Substitution

9
Elimination The goal is to see if you can eliminate a variable. 2x + y = -1 7x -5y = 5 Multiply the first equation by 5: 10x + 5y = -5 7x - 5y = 5 Add them together: 17x = 0 solve: x = 0 Substitute x into an original equation to find y: 2(0) + y = -1 y = -1 Substitute them both into the next equation to make sure your answers are correct: 7(0) – 5(-1) = 5 5 = 5

10
Substitution See if you can isolate a variable and solve for the remaining one. 2x + y = -1 7x -5y = 5 Solve the first one for y: y = -2x -1 Substitute into the second one. 7x – 5(-2x – 1) = 5 Solve 7x + 10x + 5 = 5 17x = 0 x = 0 Substitute into the first equation and solve y = -1 Substitute x & y into the 2 nd equation to be sure it works 2(0) + (-1) = -1 -1 = -1

Similar presentations

© 2022 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google